2008
DOI: 10.1016/j.anaerobe.2008.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium perfringens toxin genotypes in the feces of healthy North Americans

Abstract: We investigated the frequency of Clostridium perfringens in the normal fecal flora of healthy North Americans. About half of 43 subjects were colonized with C. perfringens at levels of approximately 10(6)cfu/g feces. Only type A strains were recovered. Spores sometimes outnumbered vegetative cells. Several genotypes were found. Some donors carried two genotypes, some only one. We found no alpha, beta2 or enterotoxin in the stools of any donors. Though some isolates carried toxin genes (e.g. cpe and cpb2) on pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 41 publications
6
55
1
3
Order By: Relevance
“…Higher concentrations of C. perfringens in human feces have also been reported previously: depending on the study, the total C. perfringens concentration in human feces ranged between 10 3 /g and 10 6-7 /g in 13% − 35% of humans tested [20]. Spores of C. perfringens were also detected in the feces of 27 of 43 healthy humans (63%) at a concentration of 10 5.5 ± 6 cfu/g [22].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Higher concentrations of C. perfringens in human feces have also been reported previously: depending on the study, the total C. perfringens concentration in human feces ranged between 10 3 /g and 10 6-7 /g in 13% − 35% of humans tested [20]. Spores of C. perfringens were also detected in the feces of 27 of 43 healthy humans (63%) at a concentration of 10 5.5 ± 6 cfu/g [22].…”
Section: Discussionmentioning
confidence: 62%
“…Three isolates of cpe-positive C. perfringens were detected among 43 fecal isolates of type A C. perfringens in a cohort of 23 healthy people [22]. Furthermore, Saito [23] suggested that humans are a possible reservoir for outbreaks of food poisoning caused by cpe-positive C. perfringens since five of 80 samples (6%) from the feces of food handlers were cpe-positive.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the demonstration that C. perfringens strains can respond to AIPs produced by other strains of this bacterium could indicate that AIPs supplied by normal gastrointestinal C. perfringens can signal disease strains to upregulate their production of toxins, like CPB, involved in intestinal infections. To this point, it is notable that previous studies (28) detected the presence of C. perfringens in the normal flora of approximately half of healthy American adults.…”
Section: Figmentioning
confidence: 99%
“…The previously isolated and characterized strains (9,15,16,(24)(25)(26) used in this study are listed in Table 1; this collection included 9 CPE-positive type A FP strains, 7 CPE-positive AAD and SD type A strains, 2 CPE-negative and 3 CPEpositive type A strains from healthy Americans, 2 CPE-negative and 1 CPE-positive type C Pig-Bel strains, and 5 CPE-positive type C Db strains. CN3718, a C. perfringens type D animal disease strain that produces epsilon toxin and all three sialidases (NanJ, NanI, and NanH), was used as a positive control for the assays of sialidase activity and Caco-2 cell adherence (21).…”
Section: Methodsmentioning
confidence: 99%